Association between HLA‐B and HLA‐DRB1 polymorphisms and systemic lupus erythematosus in Han population in China. Issue 1 (31st January 2022) - Wang, Xiangyu; Yang, Yifan; Upreti, Bibhuti; Liu, Shuang; Cui, Ruomei; Cheng, Yuqi; Tao, Li; Dong, Jing; Li, Luqiong; Xu, Jian
Abstract: We explored the association between HLA‐B and HLA‐DRB1 polymorphisms and reviewed clinical characteristics of systemic lupus erythematosus (SLE) in Han population in Yunnan, China. Methods: There were 295 patients and 265 healthy control subjects (HCs) enrolled in the study. Clinical data and blood samples were collected from the patients. The HLA‐B and HLA‐DRB1 genotypes were detected in SLE patients and HCs. Results: A total of 74 genotypes on HLA‐B loci were determined in 288 patients as well as 57 genotypes in 265 HCs. The results showed SLE was associated with the HLA‐B*40:01 and HLA‐DRB1*08:03 alleles, and the HLA‐B*46:01, HLA‐DRB1*12:02, DRB1*04:03, DRB1*14:01, DRB1*04:06, and DRB1*11:01 alleles were less likely to appear in SLE patients. Additionally, HLA‐B*07:02 and B*40:06 were associated with disease activity. HLA‐DRB1*03:01, DRB1*13:02, and DRB1*12:01 were associated with proteinuria. Furthermore, HLA‐B*51:01, B * 13:02, B * 38:02, B *35:01, HLA‐DRB1*15:02, DRB1 * 15:04, DRB1*15:01, and DRB1*08:03 were correlated with inflammatory factors and immune dysfunction. HLA‐B*15:25 was related to the production of multiple antibodies. HLA‐DRB1*12:02 might be a protective factor for pancytopenia. The haplotype of HLA‐B*40:01/DRB1*08:03 was linked with SLE. Conclusion: SLE in Han population in Yunnan province was associated with the HLA‐B*40:01 and HLA‐DRB1*08:03 alleles, and the haplotype HLA‐B*40:01/DRB1*08:03 . Several alleles were associated with inflammation, immune disorders, and organ involvement in SLE. Those alleles might be potential genetic markers of SLE. Key points: SLE in Han population in Yunnan province was associated with several alleles in HLA‐B and HLA‐DRB1 loci. Some alleles were associated with inflammation, immune disorders, and organ involvement in SLE. Abstract : HLA‐B and HLA‐DRB1 alleles are not merely susceptibility or protective genes, but also are associated with disease activity, specific system involvement, inflammation and auto‐antibodies production.